Different actions for different crimes: Explaining individual action in local crime problems. Issue 7 (31st July 2017) - Schaefer, Lacey; Mazerolle, Lorraine; Kapnoulla, Marianne
Abstract: The crime prevention literature finds extensive support for crime‐specific approaches to organized interventions in crime problems. Yet within the communities and crime literature, little is known about the crime‐specific (or generalized) way that individuals respond to different types of crime problems in their neighborhood. Using data from the Australian Community Capacity Study, this paper examines how individual characteristics, perceptions of agents of formal social control, and perceptions of informal community processes influence the decision a person makes to do something about different types of local crime problems. Results indicate that individual characteristics (prior police contact and previous victimization) and positive perceptions of informal community processes (frequency of neighboring) are positively associated with action; yet when people perceive agents of formal social control as effective, they are less likely to take informal crime control action. We conclude that the mechanisms that prompt community action are best understood from a crime‐specific approach.